HUBUNGAN PAPARAN ASAP ROKOK DENGAN TANDA-TANDA VITAL PADA BALITA DI KABUPATEN PATI - Desi Sariyani; Ana Rofika (Coping: Community of Publishing in Nursing, 2020)
Hazardous substances contained in cigarette smoke can harm the health of toddlers, especially when they are growing children are very susceptible to disease because their immune systems are still not perfect until they are past the seventh year. Children who are exposed to secondhand smoke from an early age are at increased risk of cardiovascular disease (CVD). The purpose of this study was to determine the relationship between cigarette smoke exposure and vital signs in toddlers in Pati Regency. This research is a type of correlation research with a cross-sectional design. The sample of this study was 184 toddlers whose family members were active smokers who still smoked in the house using a probability sampling technique, namely stratified random sampling. The analysis used in this study was cross-sectional with the resulting p-value <0.05. Based on the results of the analysis, it was found that there was a relationship between cigarette smoke exposure and vital signs in toddlers with a p-value of 0.000 (p <0.05. Based on the results of the study, it is suggested to increase public awareness not to smoke in the house so that it can reduce the morbidity rate in toddlers due to cigarette smoke.